Yield traits and associated marker segregation in elite introgression lines derived from O. sativa × O. nivara - Haritha, G.; Swamy, B.P.M.; Naik, M.L.; Jyothi, B.; Divya, B.; Malathi, S.; Sarla, N. (Elsevier, 2018)
Introgression lines (ILs) derived from interspecific crosses are a source of new genetic variability. A total of 55 ILs derived from two crosses Swarna × O. nivara IRGC81848 (population A) and Swarna × O. nivara IRGC81832 (population B) were characterized for yield and yield-related traits/QTLs. Segregation of 103 simple sequence repeat (SSR) markers associated with yield-related QTLs was studied. Population A showed an average of 12.6% homozygous O. nivara alleles and population B showed 10.6%. Interestingly, three SSR markers, RM223, RM128 and RM517, showed conspicuous pattern of segregation. The distribution of parental alleles at three loci RM223, RM128 and RM517 linked to yield-related traits was unique. These markers flanked to several yield-related QTLs. RM223, flanking to qyld8.3, was heterozygous in almost all the 55 ILs except in IL10-3S and IL131S. RM128 on chromosome 1 and RM517 on chromosome 3 were mutually exclusive in 46 out of 55 ILs. These 46 ILs showed either of the marker allele RM128 or RM517 from O. nivara but not both. IL166S had both RM128 and RM517 from O. nivara and the other ILs showed homozygous Swarna allele at RM517 except IL65S. Population structure assigned the 55 ILs to three sub-populations based on their genomic diversity. IL65S, IL166S, IL248S, IL7K and IL250K showed high yields in multi-location trials, and IL248S was released for cultivation as DRRDhan 40